Optimal annual net income of a containership using CO2 reduction measures under a marine emissions trading scheme. Issue 1 (February 2015) - Huang, Zehui; Shi, Xiaoning; Wu, Jingfei; Hu, Hao; Zhao, Jinsong
<x content-type="archive" xml:space="preserve">Abstract</x> Greenhouse gas (GHG) emissions from international shipping have had observable effects on the environment, which have led to an interest in market-based GHG reduction measures for international shipping. International shipping companies place key concerns and interests on exploring the future market-based GHG reduction solutions and the corresponding measures that need to be taken in advance. This paper adds to the existing literature an overview of the impact of the introduction of a Marine Emissions Trading Scheme (METS) on the choice of GHG reduction measures that can be taken by a containership and on the resulting annual net income. Technical and operational aspects are specifically considered and reflected in the alternative measures under the proposed scheme. The results of this paper try to help facilitate policy makers to devise an acceptable METS and help containerships prepare for potential to-be-implemented schemes.